Universal Representation: Systemic Benefits and the Path Ahead. (September 2019) - Nash, Lindsay
Executive Summary: At a time when politics, financial considerations, and a push for expediency put pressure on the US immigration system, it can be difficult to have faith in the adjudicatory process. Case resolution quotas, directives that constrain courts' ability to render justice in individual cases, and executive decisions that contract immigration judges' discretion contribute to an immigration system that looks less and less like judicial adjudication of some of the highest-stakes cases in our legal system and more like a ministerial claims-processing scheme. A ray of hope exists, however, in the proliferation of public defender–style systems that offer universal representation to those facing deportation. This essay describes the genesis and expansion of the universal representation movement — a project based on the idea that indigent individuals should be entitled to counsel regardless of the apparent merits or political palatability of their case. It describes the benefits of such a program to the immigration adjudication system writ large. Beyond the oft-cited increase in success rates for individuals represented and the benefits to the communities in which such programs are located, universal representation promotes the integrity of the court system and strengthens an adjudicatory procedure that, for too long, has functioned primarily to expeditiously churn through cases. Finally, looking forward, it considers some of the challenges this movement faces as it grows and it identifies areas for further expansion.